Inhibitory Effects of Eurotium cristatum on Growth and Aflatoxin B1 Biosynthesis in Aspergillus flavus - Zhao, Qiannan; Qiu, Yue; Wang, Xin; Gu, Yuanyuan; Zhao, Yuzhu; Wang, Yidi; Yue, Tianli; Yuan, Yahong (Frontiers in Microbiology, 2020)
Probiotic strain Eurotium cristatum was isolated from Chinese Fuzhuan brick-tea and tested for its in vitro activity against aflatoxigenic Aspergillus flavus. Results indicated that Eurotium cristatum can inhibit the radial growth of Aspergillus flavus. Furthermore, this inhibition might be caused by Eurotium cristatum secondary metabolites. We also observed that both radial growth of Aspergillus flavus and aflatoxin B1 production were significantly weakened following increases in the Eurotium cristatum culture filtrate concentration. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis showed that the expression of aflatoxin biosynthesis-related genes (aflD, aflQ and aflS) were down-regulated. Interestingly, cell-free supernatants of Eurotium cristatum facilitated the effective degradation of aflatoxin B1. In addition, two degradation products of aflatoxin B1 lacking the toxic and carcinogenic lactone ring were identified.